Carbon doped asymmetric cubic AlN/GaN multi quantum well structures for high electrical isolation to 3C‐SiC substrates. Issue 3 (7th February 2013) - Zado, A.; As, D. J.; Toropov, Alexey; Ivanov, Sergey
Abstract In this work we present a novel method of the electrical separation of the substrate and the hetero junction field effect transistor device. For the epitaxial growth of our structures free standing 3C‐SiC (001) substrates with a free carrier concentration of n=2.7×1018 cm‐3 and a resistivity of ρ=34 mΩcm were used. On a 50 nm c‐GaN buffer layer an asymmetric multi quantum well structure consisting of 5 periodes of two cubic GaN:C asymmetric QWs (1 nm and 2 nm) embed‐ded between 3 nm thick c‐AlN:C barriers. A 50 nm c‐GaN cap layer completes the sample structure. A detailed conduction band profile and the quantized electron states within the asymmetric quantum well were calculated using a 1D Poisson‐Schrödinger‐solver. The structural properties were analyzed by atomic force microscopy and high resolution x‐ray diffraction. Current‐voltage measurements of these structures showed an increase of the serial resistivity by six orders of magnitude (from 5 mΩ to 8 kΩ) compared to an unstructured c‐GaN reference sample. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)